A Survey of An Operative Device Aimed at Crop Approximation in the Agricultural Subdivision - Sharmila Devi, P; Periyasamy, R (International Journal of Computer Sciences and Engineering, 2025)
Agriculture is a business with risk. Crop creation depends on climatic, geographical, biological, political and monetary factors. Since of these elements there are some risks, which can be quantified when applied fitting mathematical or factual methodologies. Actually precise data about the nature of chronicled yield of crop is vital modelling input, which are helpful to ranchers & Government association for choice making process in establishing proper policies. The advances in computing and data storage hove provided vast at most of data. The challenge has been to extract learning from this crude data; this has led to new strategies and frameworks such as data mining that can bridge the learning of the data to the crop yield estimation. This research aimed to assess these new data mining frameworks and apply them to the different variables consisting in the database to establish if meaningful connections can be found.